Pola Komunikasi Etnis Besemah (Kajian Etnografi Komunikasi Pada Kelompok Etnis di Pagaralam Sumatra Selatan) - Tina Kartika (KOM & REALITAS SOSIAL, 2012)
The term of Besemah refers to the ethnic community in Gunung Dempo and Pegunungan Gumai in Pagaralam District. The Basemah ethnic surrounding in seviral provinces such as: Sumatera Selatan, Bengkulu, Jambi, Bangka Belitung, and Lampung. the Basemah ethnic knows the oral messages through guritan,petata/petiti/proverbs,and anday-anday/folklores.The Basemah ethnic knows the tabbo languages, one of . those taboo languages is singkuh. So that, this studi the best use the etnografi communication theory.The theoritical fundations used are:symbolism interaction,Social Construction of Reality. and communication ethnography Dell Hymes.The research method is qualitative with interpretive paradigm. The research focus is how is the communication pattern of Basemah Ethnic in Jangkar village. Jangkar Mas North Dempo, Pagaralam.The research results show that the communication activity of Basemah ethnic in.Jangkar village was built from communicative events, communicative situation and communicative acts. From the relationship of those communicative components, it is obtainet the communicative patterns,which are: 1) The communication pattern of Basemah Ethnic family care. 2) Communication pattern of Keluarge Pasat of Basemah Ethnic. 3)The communication behavior pattern of Singkuh in at Basemah Ethnic. 4) the communication behavior through pepatah jeme tue tue, 5) The message. pattern in Basemah ethnic. and 6) The communication pattern among Basemah Ethnic.